Paediatrics: how to manage viral gastroenteritis - Alexander KC Leung; Kam Lun Hon (BioExcel Publishing Ltd, 2021)
Background: Viral gastroenteritis is the most common diarrhoeal disorder seen in general practice and emergency departments. This article aims to provide a narrative updated review on the evaluation and management of viral gastroenteritis in children. Methods: A PubMed search was performed with Clinical Queries using the key term 'viral gastroenteritis'. The search strategy included clinical trials, meta-analyses, randomized controlled trials, observational studies and reviews. The search was restricted to the English literature and the paediatric population. Results: Acute viral gastroenteritis is usually self-limiting. However, it can lead to dehydration and electrolyte imbalance if not properly treated. Adequate fluids containing physiological concentrations of glucose and electrolytes should be provided to compensate for gastrointestinal losses and cover maintenance needs. Oral rehydration therapy is as effective as intravenous (IV) fluid therapy for rehydration for children with mild-to-moderate dehydration. Measurements of serum electrolytes, creatinine and glucose are usually not necessary and should only be considered in a subset of children with severe dehydration who require hospitalization and IV therapy. Judicious use of ondansetron can increase the success rate of oral rehydration therapy and minimize the need for IV therapy and hospitalization. Conclusion: Acute viral gastroenteritis is associated with substantial morbidity in developed countries and significant mortality in developing countries. Physicians should educate caregivers on proper personal hygiene and handwashing to prevent faecal to oral transmission of the pathogen as well as the importance of rotavirus vaccine in the prevention of rotavirus gastroenteritis. Several norovirus vaccines are currently undergoing clinical trials with promising results. It is hoped that development of an effective norovirus vaccine will further reduce the incidence of viral gastroenteritis.